Spatial Distribution of Historical and Cultural Resources and Regional Revitalization Strategies in Chungcheong Province, South Korea - Byoungjin Kim; Donghwa Shon (Land)
This study quantitatively analyzed the spatial characteristics of 3425 historical and cultural resources across the Chungcheong region of South Korea and proposed strategies for regional revitalization. Each asset was evaluated on a five-point scale, and spatial patterns were examined using kernel density estimation (KDE), Moran’s I, and Local Indicators of Spatial Association (LISA). The results show that the historical and cultural resources in the Chungcheong region form significant clusters, particularly in areas such as Boryeong, Seosan, Gongju, and Buyeo, which were historically associated with administrative, Confucian, and Buddhist functions. A Moran’s I value of 0.272 was obtained, indicating statistically significant spatial autocorrelation, and the LISA analysis identified “high–high” clusters as key zones with concentrated high-value assets. This study also revealed mismatches between designated cultural properties and areas with high-value but unrecognized resources, emphasizing the need for more inclusive heritage policies. These findings suggest that historical resources should be understood not as isolated sites, but as interconnected cultural landscapes. This research supports the development of tailored, place-based urban regeneration strategies that leverage cultural heritage as a foundation for sustainable regional identity and growth.